The Australian Prices justification tribunal - Nieuwenhuysen, J. P.; Daly, Anne Elizabeth (Carlton, Australia : Melbourne University Press, 1977)
In this book, the authors review the background to the creation of the tribunal in 1973. Chapter 2 takes a brief view of the rationale of price surveillance. Chapter 3 surveys the changeable and rather vague criteria employed by the tribunal in its open forums- the public inquiries. Chapter 4 catalogues the available information on hearings behind closed doors. Chapter 5 documents the experience of Australia's largest company, BHP, with the tribunal, and also the results of a small survey of four companies which had dealings with the tribunal. Chapter 6 covers the changing attitude of governments between 1973 and 1976 towards the tribunal and other disparate bodies concerned with economic policy. Chapter 7 deals with wage costs and the tribunal. Chapter 8 delves further by examining the role of unions in the activities of the tribunal. Chapter 9 considers it useful to include a discussion of some aspects of British and American experience so as to highlight, in a comparison of different institutional forms, the advantages of each.
Includes index.
Includes bibliographical references: p. 225-227.
ne 17/05/2018
Loans
Keywords: Price regulation